Implementasi Metode Waterfall untuk Sistem Penjadwalan Perkuliahan pada Universitas Muhammadiyah Bima - Iis Muzdalifah; Teguh Ansyor Lorosae; Irma Eryanti Putri (LKP Unity Academy, 2025)
Course scheduling is a crucial activity in academic management because it involves organizing lecturers, courses, classrooms, and time allocations in an integrated manner. At Universitas Muhammadiyah Bima, the scheduling process was still conducted manually using spreadsheets, resulting in frequent schedule conflicts, repeated revisions, and inefficient management processes. This study aims to design and implement a web-based course scheduling system capable of overcoming these problems through an automatic constraint-based validation mechanism. The system was developed using the CodeIgniter 4 framework and the Waterfall development method. The main contribution of this research lies in the implementation of real-time automatic validation capable of detecting and preventing conflicts involving lecturers, classrooms, and class schedules before the data are stored in the database, thereby producing a more consistent and reliable scheduling process compared to the previous manual method. System testing was carried out using the Black-box Testing method on 10 testing scenarios covering input validation, schedule conflict detection, data manipulation, and schedule information access. The testing results showed that all scenarios were successfully executed with a success rate of 100%, indicating that all system functions operated in accordance with user requirements. Therefore, the developed system is able to improve the effectiveness of course scheduling management while minimizing scheduling conflicts within the academic environment.